2020
DOI: 10.3389/fimmu.2019.03161
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle lncRNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 Released From Glioma Stem Cells Modulates the Inflammatory Response of Microglia After Lipopolysaccharide Stimulation Through Regulating miR-129-5p/High Mobility Group Box-1 Protein Axis

Abstract: Glioma stem cell (GSC)-derived extracellular vesicles (EVs) can mediate the communication between GSCs and microglia. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) expression in GSCs, EVs, and supernatant was detected by real-time PCR. The direct targeting between MALAT1 and miR-129-5p, miR-129-5p, and HMGB1 were tested with luciferase reporter analysis. The expression and secretion of interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-α were determined in lipopolysaccharide-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The miR-129-5p/HMGB1 axis is widely involved in biological processes such as inflammation, cell proliferation and autophagy, and affects the progression of several diseases including chronic constriction injuries, cerebral hemorrhage and lung cancer. 8,1721…”
Section: Discussionmentioning
confidence: 99%
“…The miR-129-5p/HMGB1 axis is widely involved in biological processes such as inflammation, cell proliferation and autophagy, and affects the progression of several diseases including chronic constriction injuries, cerebral hemorrhage and lung cancer. 8,1721…”
Section: Discussionmentioning
confidence: 99%
“… 194 Studies have shown that glioblastomas are infiltrated with a large number of microglial cells, which interact with glioblastomas and induce tumor immunosuppression. 195 Recently, a study performed by Yang and his colleagues demonstrated that EVs lncRNA MALAT1 released from GSCs mediated LPS-induced inflammatory response of microglia by targeting miR-129-5p/HMGB1 (high mobility group box-1) protein alix. 195 When co-incubating with GSCs-derived EVs, IL-6, IL-8, and TNF-α secreted by LPS-stimulated microglial increased significantly.…”
Section: The Biological Roles Of Cscs-derived Evsmentioning
confidence: 99%
“…Decidual natural killer cells (dNKs) account for approximately 70% of the immune cells at the maternal–fetal interface, comprise the largest specific immune cell population and decrease with increasing gestational age 8 . dNK cells are distinct from the majority of peripheral blood NK cells (pNKs).…”
Section: Introductionmentioning
confidence: 99%
“…dNK cells are distinct from the majority of peripheral blood NK cells (pNKs). Approximately 90% of pNKs have a CD56 dim CD16 + surface phenotype that represents cytotoxic NK cells 8 , but almost all dNKs are CD56 + CD16 – 9 , representing cytokine-producing NK cells. The presence of dNKs in early pregnancy can help the decidualization of the endometrium and the invasion of trophoblasts 9 .…”
Section: Introductionmentioning
confidence: 99%